Looking for/Longing for/Sick for Home: Marina Tsvetaeva in English Translation. (November 2014) - Bergin, Tara; Tsvetkova, Marina; Whyte, Christopher
Abstract : This contribution consists of a correspondence between a postdoctoral English literature scholar and poet, Tara Bergin, and a Russian and English literature scholar, Marina Tsvetkova, who initially set out to write an essay comparing two translations of Tsvetaeva's poem of May 1934, called 'Homesickness' by Elaine Feinstein and 'Longing for the Motherland' by David McDuff. Their letters focus on this poem but also venture into Tsvetaeva's biography and some of her other writings. Eventually it seemed to them appropriate to submit for publication the correspondence itself, following which the material was given a detailed reading by a third Tsvetaeva translator, Christopher Whyte. His comments are also published here, with a postscript from the two correspondents.